1991
DOI: 10.1099/0022-1317-72-6-1349
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of 42 kbp of vaccinia virus strain WR from near the right inverted terminal repeat

Abstract: The nucleotide sequence of 42 090 bp of vaccinia virus strain WR is presented. The sequence includes the SalI L, F, G and I fragments and starts near the centre of the HindIII A fragment and extends rightwards towards the genomic terminus, finishing approximately 0-5 kb internal of the inverted terminal repeat (ITR). Translation of this region has identified 65 open reading frames (ORFs) of greater than 65 amino acids in length. Fifty-one of these which do not extensively overlap other larger ORFs have been su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 138 publications
(111 reference statements)
3
107
0
Order By: Relevance
“…The partial ORFs located at either end of the BamHI H fragment, designated H0R and H4R, also potentially encode proteins similar in sequence to various poxvirus and cellular proteins. The H4R ORF product displayed 29-2~0 amino acid identity with the erythrocyte ankyrin protein• The H0R ORF, which overlaps the amino terminus of the H IR ORF, encodes a protein with similarity to the carboxy-terminal portion of the vaccinia virus B5R ORF product Smith et al, 1991), also referred to as the plaque size/host range gene product for the Lister strain of vaccinia virus (Takahashi-Nishimaki et al, 1991). The similarity to the Lister protein (shown in Table 1) is higher due to several amino acid differences compared to the vaccinia virus WR strain protein, which are also conserved in the SFV ORF product.…”
Section: Resultsmentioning
confidence: 99%
“…The partial ORFs located at either end of the BamHI H fragment, designated H0R and H4R, also potentially encode proteins similar in sequence to various poxvirus and cellular proteins. The H4R ORF product displayed 29-2~0 amino acid identity with the erythrocyte ankyrin protein• The H0R ORF, which overlaps the amino terminus of the H IR ORF, encodes a protein with similarity to the carboxy-terminal portion of the vaccinia virus B5R ORF product Smith et al, 1991), also referred to as the plaque size/host range gene product for the Lister strain of vaccinia virus (Takahashi-Nishimaki et al, 1991). The similarity to the Lister protein (shown in Table 1) is higher due to several amino acid differences compared to the vaccinia virus WR strain protein, which are also conserved in the SFV ORF product.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure revealed the presence of five proteins with apparent Mrs of 60K, 43K, 28K, 18K and 14-5K with affinity for viral core mRNA. A ribonucleoprotein (RNP) with a typical RNA-binding motif and an Mr of 14-2K was predicted within the genome of vaccinia virus Copenhagen strain (A31R) (Goebel et al, 1990) and an equivalent protein was found in the WR strain (SalL1 R) with an apparent Mr of 14"9K (Smith et al, 1991). The possibility of this protein being one of the proteins identified in this work, and the formation of RNAprotein complexes during in vitro mRNA synthesis, are discussed.…”
Section: Introductionmentioning
confidence: 91%
“…There are two cellular TNFRs which each have an external domain consisting of four repeats of a cysteine-rich motif followed by a transmembrane anchor sequence and different cytoplasmic domains for signal transduction. The sequence of vaccinia virus strain WR shows that ORF SalF19R (A53R in Copenhagen) is related to the external domain of TNFR but the repeated domains are fragmented by frameshift and nonsense mutations (Howard et al, 1991). Similarly, the complete sequence of vaccinia virus strain Copenhagen (Goebel et al, 1990) shows an ORF identical to WR SalF19R and another ORF related to TNFR within each ITR (C22L and B28R) .…”
Section: Soluble Cytokine Receptorsmentioning
confidence: 99%
“…Vaccinia virus nucleotide sequence data predict that several other genes encode secretory proteins that may be glycosylated (Goebel et al, 1990;Howard et al, 1991;.…”
Section: Secretorymentioning
confidence: 99%